2022
DOI: 10.3389/fmed.2022.879425
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Enoxaparin for Systemic Anticoagulation of COVID-19 Patients During Extracorporeal Life Support

Abstract: BackgroundExtracorporeal membrane oxygenation, with an inherent requirement for anticoagulation to avoid circuit thrombosis, is a key element in the treatment of respiratory failure associated with COVID-19. Anticoagulation remains challenging, the standard of care being intravenous continuous administration of unfractionated heparin. Yet regimens vary. Some intensive care units in our center have successfully used enoxaparin subcutaneously in recent years and throughout the pandemic.MethodsWe retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Subcutaneous administration of anticoagulation was associated with thrombotic complications (both combined and individual), suggesting that this route might not be suitable for preventing thrombosis in COVID-19 ECMO patients. This finding contrasts with Wiegele et al 's single-center study, where ECMO patients treated with subcutaneous enoxaparin experienced fewer thrombotic or major bleeding events than those receiving unfractionated heparin [20].…”
Section: Discussioncontrasting
confidence: 78%
“…Subcutaneous administration of anticoagulation was associated with thrombotic complications (both combined and individual), suggesting that this route might not be suitable for preventing thrombosis in COVID-19 ECMO patients. This finding contrasts with Wiegele et al 's single-center study, where ECMO patients treated with subcutaneous enoxaparin experienced fewer thrombotic or major bleeding events than those receiving unfractionated heparin [20].…”
Section: Discussioncontrasting
confidence: 78%
“…Recently, although heparin, especially LMWH, seemed to perform well in anticoagulation and has been recommended in hospitalized COVID-19 patients. 17 , 30 34 However, early evidence demonstrates that COVID-19 patients are at high risk for thrombosis, even those receiving standard or intensified thromboprophylaxis doses with LMWH or UFH. 35 In addition, heparin tolerance or resistance has become an ongoing problem in anticoagulation therapy for COVID-19, which makes it more difficult to monitor.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of life-threatening hemorrhage, blood product transfusion, and the risk of thromboembolic events should be taken into consideration when initiating systemic anticoagulation. In well-selected patients, the use of reduced anticoagulation by using low-dose heparin only or different dosages of LMWH is being investigated [ 75 , 76 , 77 , 78 ].…”
Section: Anticoagulation Strategiesmentioning
confidence: 99%
“…Moreover, patients receiving LMWH had a lower risk of thromboembolic events [ 77 ]. Finally, Wiegele et al compared the use of heparin and enoxaparin (2 × 4000 IU, anti-Xa level monitored) in COVID-19 patients and concluded that the subcutaneously administered enoxaparin is superior (given the rate of adverse events) when compared to UFH, and may be seen as a possible anticoagulation strategy in COVID-19 patients requiring ECMO support [ 78 ].…”
Section: Anticoagulation Strategiesmentioning
confidence: 99%